2010
DOI: 10.1080/07481187.2010.482879
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Parents Readjusting to the Workplace Following the Death of a Child by Suicide

Abstract: Suicide among young people has become a growing concern in life in the 21st century and is a tragedy faced by an increasing number of families and in particular parents. This study set out to focus on the experiences of parents reentering the workplace following the death of a child by suicide. Although the immediate aftermath of experiencing traumatic death has been studied, we know less about the longer-term effects on life tasks such as returning to work. A sample of bereaved parents was interviewed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Most would therefore experience continuing or periodic intense mourning following the death and for some time afterward, as people can take up to 2 years to recover (Zhang et al., 2006). Some would also be emotionally distraught and physically tired for some time because of being an informal caregiver up to and perhaps also during the final dying process (Gibson et al., 2010). With only 43.8% of deaths in Canada taking place in hospital now (Wilson, Shen, & Birch, 2017), much more end-of-life care is taking place in the home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most would therefore experience continuing or periodic intense mourning following the death and for some time afterward, as people can take up to 2 years to recover (Zhang et al., 2006). Some would also be emotionally distraught and physically tired for some time because of being an informal caregiver up to and perhaps also during the final dying process (Gibson et al., 2010). With only 43.8% of deaths in Canada taking place in hospital now (Wilson, Shen, & Birch, 2017), much more end-of-life care is taking place in the home.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, little attention has focused on the impact of bereavement grief on work, careers, and the workplace, although most people are likely to experience the death of parents, friends, and other loved ones over their work lives (Gibson, Gallagher, & Jenkins, 2010; Wilcox, Mittendorfer-Rutz, Kjeldgard, Alexanderson, & Runeson, 2015). No published or unpublished reports on the incidence of bereavement leaves from work in Canada or any other developed country could be found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when bereaved employees return to work they may function at a reduced level (CharlesEdwards, 2005). A study carried out in Northern Ireland, limited by its sample size of only 11 parents and only exploring one form of bereavement, suicide of a child, estimated required time off work ranged from one to 12 weeks (Gibson, Gallagher, & Jenkins, 2010). Time off work for bereavement is challenging to assess and there is a resultant paucity of research on the socio-economic impact of bereavement on individuals and businesses, with Scotland no exception in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Even highly motivated men, who registered for work soon , did not get work quickly . A study of parents readjusting to the workplace following death of a child by suicide showed gender differences in motivation and behavior, likely to have long-term impact on their working lives and earnings (Gibson et al, 2010). Some bereaved parents needed to pursue different kinds of work, for example, when work involving children was too distressing (Harper, 2010).…”
Section: Changes In Economic Role and Responsibilitiesmentioning
confidence: 99%